The Vitruvian Manifold: Inferring Dense Correspondences for One-Shot Human Pose Estimation - Taylor, Jonathan; Shotton, Jamie; Sharp, Toby; Fitzgibbon, Andrew (Proc. CVPR, 2012)
Fitting an articulated model to image data is often approached as an optimization over both model pose and model-to-image correspondence. For complex models such as humans, previous work has required a good initialization, or an alternating minimization between correspondence and pose. In this paper we investigate one-shot pose estimation: can we directly infer correspondences using a regression function trained to be invariant to body size and shape, and then optimize the model pose just once? We evaluate on several challenging single-frame data sets containing a wide variety of body poses, shapes, torso rotations, and image cropping. Our experiments demonstrate that one-shot pose estimation achieves state of the art results and runs in real-time.